NATURAL HAZARD ELIMINATION USING ELECTROCHEMICAL PROPERTIES – WATER FLOOD - Imadeldin Elmutasim; Mohamad Shaiful; Izzeldin Mohamed; Khalid Bilal; Mohamed Hassan (Journal of Mechanics of Continua and Mathematical Sciences)
A combination of science is a way to accommodate various effective phenomena that could influence the entire life cycle. Recently, emphasis has been placed on the electrochemical polymerization mechanism that is involved in numerous technological applications, including sensors and detectors. Accordingly, daily promises were raised to eliminate life disasters and alleviate the challenges such as water floods as a part of weather changes, which could cause severe damage to life health explicitly, infrastructure, economic productivity, and much more. The proposal considers the matter via compromising the water overflow as well as eliminating the disaster that would come in no warning time and tackling the climate emergency flooding with the potential of water reclamation and offers scholarly suggestions by the requirements of the scientific approach. The investigation clarified the electromagnetic absorber beside the electrochemical polymerization through engagement in the flooded water track stations and the calculation result shows that 19.73% could be absorbed when using 300 grams of polymer gel capacity in 240 grams of water. Generally, the paper explores the electromagnetic flood disaster and how to address it to build a more secure forthcoming.